EFFECT OF GELAM LEAF EXTRACT (Melaleuca cajuputi) AND TRICALCIUM SILICATE CEMENT AS DIRECT PULP CAPPING - Emma Annahal Husma; Sherli Diana; Debby Saputera; Maharani Laillyza Apriasari; Tri Nurrahman (Dentino: Jurnal Kedokteran Gigi, 2024)
Background: Reversible pulpitis is mild pulp inflammation. The treatment is direct pulpcapping. Tricalcium silicate cement has been better at inducing reparative dentin than other materials. Tricalcium silicate cement can cause inflammation 1-2 weeks after application, that natural ingredients need to improve the quality. Tricalcium silicate cement can be combined with galam leaf extract which contains anti-inflammatory properties by accelerating lymphocyte cells. Purpose: To analyzed the effect of gelam leaf extract (Melaleuca cajuputi) concentration of 100% and Tricalcium Silicate Cement on the number of lymphocyte cells on day 3 and 5 in direct pulp capping treatment. Methods: This research is a true experimental study with a post test-only with control design. This study used 24 Wistar rats, divided into 3 treatment groups with 2 different days, namely the group given a combination of Gelam leaf 100% + tricalcium silicate cement, tricalcium silicate cement as positive control, and without treatment as negative control. Results: One-way ANOVA test obtained p value=0.00<0.05, which indicates there is a significant difference between each group. Post Hoc Bonferroni test showed significant difference between galam leaf extract and tricalcium silicate cement, tricalcium silicate cement, and no treatment on days 3 and 5. Conclusion: The combination of galam leaf extract and tricalcium silicate cement can increase the number of lymphocyte cells on day 3 of pulp inflammation and reduce the number of lymphocyte cells on day 5 more effectively than tricalcium silicate cement and without treatment on days 3 and 5 so that the healing process is faster.